2013
DOI: 10.1111/mpp.12000
|View full text |Cite
|
Sign up to set email alerts
|

TGBp3 triggers the unfolded protein response and SKP1‐dependent programmed cell death

Abstract: The Potato virus X (PVX) triple gene block protein 3 (TGBp3), an 8-kDa membrane binding protein, aids virus movement and induces the unfolded protein response (UPR) during PVX infection. TGBp3 was expressed from the Tobacco mosaic virus (TMV) genome (TMV-p3), and we noted the up-regulation of SKP1 and several endoplasmic reticulum (ER)-resident chaperones, including the ER luminal binding protein (BiP), protein disulphide isomerase (PDI), calreticulin (CRT) and calmodulin (CAM). Local lesions were seen on leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 94 publications
3
63
0
1
Order By: Relevance
“…The plant UPR comprises two branches, one mediated by IRE1 and the other by ATF6-like receptors, which involves the transcription factors bZIP17 and 28 (Howell, 2013). Viral infection in plants is known to induce the IRE1 arm of UPR, which involves IRE1-mediated splicing of bZIP60 mRNA, resulting in the synthesis of a functional bZIP protein that can activate ER stress-inducible promoters in the nucleus (Ye et al, , 2013Verchot 2014). Examples include induction of bZIP60 and UPR chaperone gene expression by the ER associated movement protein of potato virus X and the turnip mosaic virus 6K2 protein-induced splicing of bZIP60 mRNA .…”
mentioning
confidence: 99%
“…The plant UPR comprises two branches, one mediated by IRE1 and the other by ATF6-like receptors, which involves the transcription factors bZIP17 and 28 (Howell, 2013). Viral infection in plants is known to induce the IRE1 arm of UPR, which involves IRE1-mediated splicing of bZIP60 mRNA, resulting in the synthesis of a functional bZIP protein that can activate ER stress-inducible promoters in the nucleus (Ye et al, , 2013Verchot 2014). Examples include induction of bZIP60 and UPR chaperone gene expression by the ER associated movement protein of potato virus X and the turnip mosaic virus 6K2 protein-induced splicing of bZIP60 mRNA .…”
mentioning
confidence: 99%
“…, ; Ye et al. , ). Similarly, we propose that co‐infections of PVX with other viruses expressing strong VSRs could mimic HC‐Pro action on P25, allowing P25 to accumulate to very high levels with a detrimental effect on ER homeostasis, subsequently leading to necrosis in systemic leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have shown that the TGB3 protein of PVX triggers UPR and elicits PCD when expressed from TMV or under the control of the CaMV 35S promoter and delivered by agroinfiltration into N. benthamiana (Ye et al. , ). These findings argue that PVX encodes at least two protein products, TGB3 and P25, capable of inducing a UPR and cell death when overexpressed by either a viral vector or in the presence of a strong VSR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silencing SKP1 directly alters the level of virus accumulation and systemic necrosis in tobacco plants. While the role of ubiquitin in this process is not established, the role of the proteasome in viral protein turnover is inferred [48,50]. These examples of TYMV, TMV and PVX demonstrate that the UPS can be subverted by some viruses to ensure cellular homeostasis and cell survival needed by both the plant and the virus to co-exist.…”
Section: Ubiquitin Proteasome System Supporting Virus Replication mentioning
confidence: 99%